2016
DOI: 10.17159/0379-4350/2016/v69a15
|View full text |Cite
|
Sign up to set email alerts
|

Determination of mercury in selected polluted sediments using HPLC-ICP-MS in Westbank area, Western Cape, South Africa

Abstract: High selectivity, excellent linearity and reproducibility were achieved using HPLC-ICP-MS method for mercury in sediments. The HPLC-ICP-MS method reported previously for mercury in biota analysis was adapted in terms of operational consumables and optimized for the efficient mercury determination in riverbed sediments; a first for South Africa. Results obtained for real environmental samples, were verified by Direct Mercury Analysis (DMA) by an accredited laboratory. The determination of inorganic and organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The problems can be overcome by modifying the shape and size of the commercial gas liquid separator (Panggabean et al, 2013). Gas liquid Separator modified was expected to improve the performance of measurement results to the maximum Several studies on determination of Hg in various samples using CV-AAS technique has been reported, such as: determination of Hg level in fish (Chen et al, 2013;Da Silva et al, 2019;Fashi et al, 2017;Zhu et al, 2017), groundwater and river using electrochemical CV-AAS technique (Karthika et al, 2019;Some et al, 2016), oil samples (Payehghadr et al, 2014;Veronesi et al, 2013;Vicentino et al, 2015), environmental samples (Gao et al, 2012;Le Roux et al, 2016;Oreste et al, 2013), hair (Domanico et al, 2017), determination of Hg level in honey, pollen, and greek bees (Maragou et al, 2016), and seafood using photochemical vapor generation capacitively coupled plasma microtorch optical emission spectrometry (Covaci et al, 2017), reported that the results obtained are valid and can be justified.…”
Section: Introductionmentioning
confidence: 99%
“…The problems can be overcome by modifying the shape and size of the commercial gas liquid separator (Panggabean et al, 2013). Gas liquid Separator modified was expected to improve the performance of measurement results to the maximum Several studies on determination of Hg in various samples using CV-AAS technique has been reported, such as: determination of Hg level in fish (Chen et al, 2013;Da Silva et al, 2019;Fashi et al, 2017;Zhu et al, 2017), groundwater and river using electrochemical CV-AAS technique (Karthika et al, 2019;Some et al, 2016), oil samples (Payehghadr et al, 2014;Veronesi et al, 2013;Vicentino et al, 2015), environmental samples (Gao et al, 2012;Le Roux et al, 2016;Oreste et al, 2013), hair (Domanico et al, 2017), determination of Hg level in honey, pollen, and greek bees (Maragou et al, 2016), and seafood using photochemical vapor generation capacitively coupled plasma microtorch optical emission spectrometry (Covaci et al, 2017), reported that the results obtained are valid and can be justified.…”
Section: Introductionmentioning
confidence: 99%
“…Many methods have been reported for the determination of mercury such as high chromatography-inductively coupled plasma mass spectrometry (HPLC/ICP-MS) [13,14], gas chromatography-mass spectrometry (GC/MS) [2,15], graphite furnace atomic adsorption spectrometry (GF-AAS) [5,16,17], cold vapor atomic absorption spectrometry (CV-AAS) [3,9,18,19], cold vapor atomic fluorescence spectrometry (CV-AFS) [4,20,21], chemical vapor generation atomic emission spectrometry (CVG-AES) [22], UV-Vis spectrophotometric [23,24], and anodic stripping voltammetry (ASV) [25][26][27][28][29][30][31][32][33][34][35][36]. Compared to the ASV methods, the HPLC-MS and GC-MS methods require complex sample preparations and the use of toxic organic solvents (e.g., methanol and acetonitrile), and the analytical is also more complex.…”
Section: Introductionmentioning
confidence: 99%